1: Subtract: (-4y2-3y+8) – (2y2-6y+2)
A: Here we are just asked to clean things up and combine like terms: basically, add apples with apples and oranges with oranges, but don’t accidentally add apples with oranges!
y2 terms get combined with y2 terms
y terms get combined with y terms
constants (lone numbers) get combined with constants
So, let’s use color to highlight the like terms:
(-4y2-3y+8) – (2y2-6y+2)
How many total y2 terms do you have? -4y2 – 2y2 = -6y2
How many total y terms do you have? -3y – -6y = -3y+6y = 3y
How many total constant terms do you have? 8 – +2 = 8 – 2 = 6
Did we forget anyone? Did anyone not have a match that we need to bring along? Nope! Everyone from both sets of parentheses is accounted for!
So, final answer:
(-4y2-3y+8) – (2y2-6y+2) = -6y2 + 3y + 6